2007
DOI: 10.1213/01.ane.0000260307.16555.7f
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Lumbar Epidural Steroid Injections in Patients with Lumbar Disc Herniations

Abstract: The TF route of epidural steroid placement is more effective than the C or IL routes. We attribute this observation to a higher incidence of steroid placement in the ventral epidural space when the TF method is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
190
1
9

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 250 publications
(205 citation statements)
references
References 12 publications
5
190
1
9
Order By: Relevance
“…The contradictory results of the studies to date may be explained by numerous methodological faults and technical deficiencies [18,19,21,22]. Studies by Ackerman and Ahmad [23] and Schaufele et al [19] have proved that the TF approach is more efficient than the IL approach in the application of steroids. In our study, based on assessments of strongest and current pain during the previous 4 months, we cannot come to such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…The contradictory results of the studies to date may be explained by numerous methodological faults and technical deficiencies [18,19,21,22]. Studies by Ackerman and Ahmad [23] and Schaufele et al [19] have proved that the TF approach is more efficient than the IL approach in the application of steroids. In our study, based on assessments of strongest and current pain during the previous 4 months, we cannot come to such a conclusion.…”
Section: Discussionmentioning
confidence: 99%
“…Prior data has shown that transforaminal injections produce superior results compared to caudal or interlaminar approach [52]. In an effort to enhance the success of this treatment, recent literature has examined the role of patient position during epidural CSI injection.…”
Section: Treatment Non-operativementioning
confidence: 99%
“…Description of epidural/intradiscal injection studies Summary of interventions Sixty-three studies evaluated the use of epidural/intradiscal injection for sciatica 95, (eight studies had more than two treatment arms 146,149,161,163,167,169,183,197 181,[183][184][185]187,193,194,197,200,202 (two studies had more than two treatment arms 183,197 ) compared different modes of administering epidural/intradiscal injections and 20 studies 149,167,[177][178][179][180]182,186,[188][189][190][191][192]195,196,198,199,203,204,207 compared the use of different epidural/intradiscal injections. Details of the interventions are summarised in Table 17b, but the findings of these studies are not considered any further here.…”
Section: Epidural/intradiscal Injectionmentioning
confidence: 99%